Agroecological horticulturists in mountain environments of the municipality of Teresópolis, Rio de Janeiro, Brazil - Oliveira, Elton de; Aquino, Adriana Maria de; Assis, Renato Linhares de; Mello, João Carlos Correia Baptista Soares de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The municipality of Teresópolis, in the Rio de Janeiro mountain region, stands out in the production of vegetables, has all its agricultural activity in mountain environments, where the great intensity of crops causes disturbing environmental problems. The technologies based on agroecology propose actions that can improve the performance of agriculture in these environments. However, to support these actions, there is a need to study and better understand the productive dynamics in these environments. The objective of this work is to analyze the performance of agroecological production units (PUs), using the Data Envelopment Analysis (DEA) methodology, for a case study. The variables of cultivated area, external inputs, machine hours and man days as inputs were used; invoicing and different items produced, as outputs of the DEA model applied. The UP that presented the best performance, produced 34 different items, was efficient during nine months, with an efficiency index of 96%, in the year 2017. The combination or sequence between the types of crops, size of the areas destined to each one and times of planting constitute a productive dynamic capable of promoting the efficiency of each UP. The identification of efficient units and the understanding of the dynamics and the good productive practices, can help the farmers with less efficiency, in the improvement of the performance.